Improving prognostic evaluations in patients with stage IIIb light chain cardiac amyloidosis: role of haemodynamic parameters - Jingyi Li; Yang Lu; Xiqi Xu; Zhuang Tian; Jian Li; Shuyang Zhang (Orphanet Journal of Rare Diseases)
Abstract Background There is no unified prognostic scoring system for light chain cardiac amyloidosis (AL-CA), particularly stage IIIb AL-CA. This study aimed to use invasive haemodynamic information to investigate markers that can more accurately evaluate the prognosis of patients with stage IIIb AL-CA. Methods In this retrospective cohort study, we conducted invasive haemodynamic measurements concurrently with myocardial biopsies to diagnose AL-CA. We used Cox regression analysis and time-dependent receiver operating characteristic curve analysis to study the associations between these measurements and overall mortality. Echocardiographic parameters were also recorded and analysed via logistic regression to explore their relationships with haemodynamic changes. Results Although traditional haemodynamic parameters, such as the cardiac index (CI), pulmonary artery wedge pressure (PAWP), pulmonary artery pressure, and vascular resistance, did not correlate with mortality, the PAWP/CI ratio emerged as a vital prognostic marker. Patients with a PAWP/CI ratio above 11 mmHg/L/min/m2 had markedly poorer survival. Kaplan‒Meier analysis highlighted the prognostic significance of the ratio, revealing distinct survival differences. Furthermore, logistic regression confirmed that echocardiographically measured pulmonary artery systolic pressure independently correlated with increases in the PAWP/CI ratio. Conclusions In stage IIIb AL-CA patients, the PAWP/CI ratio, which surpasses traditional haemodynamic indicators, significantly predicts all-cause mortality, emphasizing its prognostic value. Our findings suggest that echocardiography-derived PASP could alternatively reflect the PAWP/CI ratio.